Guava Waste to Sustain Guava (Psidium guajava) Agroecosystem: Nutrient “Balance” Concepts - Souza, Henrique A.; Parent, Serge-Étienne; Rozane, Danilo E.; Amorim, Daniel A.; Modesto, Viviane C.; Natale, William; Parent, Leon E. (Frontiers in Plant Science, 2016)
The Brazilian guava processing industry generates 5.5 M Mg guava waste yr-1 that could be recycled sustainably in guava agro-ecosystems as slow-release fertilizer. Our objectives were to elaborate nutrient budgets and to diagnose soil, foliar and fruit nutrient balances in guava orchards fertilized with guava waste. We hypothesized that (1) guava waste are balanced fertilizer sources that can sustain crop yield and soil nutrient stocks, and (2) guava agroecosystems remain productive within narrow ranges of nutrient balances. A 6-yr experiment was conducted in 8-yr old guava orchard applying 0-9-18-27-36 Mg ha-1 guava waste (dry mass basis) and the locally recommended mineral fertilization. Nutrient budgets were compiled as balance sheets. Foliar and fruit nutrient balances were computed as isometric log ratios to avoid data redundancy or resonance due to nutrient interactions and closure to measurement unit. The N, P and several other nutrients were applied in excess of crop removal while K was in deficit whatever the fertilizer treatment. The foliar diagnostic accuracy of reached 93 % using isometric log ratios and knn classification, generating reliable foliar nutrient and concentration ranges at high yield level. The plant mined the soil K reserves without any significant effect on fruit yield and foliar nutrient balances involving K. High guava productivity can be reached at lower soil test K and P values than thought before. Parsimonious dosage of fresh guava waste should be supplemented with mineral K fertilizers to recycle guava waste sustainably in guava agroecosystems. Brazilian growers can benefit from this research by lowering soil test P and K threshold values to avoid over-fertilization and using fresh guava waste supplemented with mineral fertilizers, especially K. Because yield was negatively correlated with fruit acidity and Brix index, balanced plant nutrition and fertilization diagnosis will have to consider not only fruit yield targets but also fruit quality to meet requirements for guava processing.